2011
DOI: 10.1523/jneurosci.6759-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Movement Observation Improves Early Consolidation of Motor Memory

Abstract: Practicing a motor task can induce neuroplastic changes in the human primary motor cortex (M1) that are subsequently consolidated, leading to a stable memory trace. Currently, little is known whether early consolidation, tested several minutes after skill acquisition, can be improved by behavioral interventions. Here we test whether movement observation, known to evoke similar neural responses in M1 as movement execution, can benefit the early consolidation of new motor memories. We show that observing the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…Alternatively, in our study, motor performance differences between groups could have decreased due to a time-based dissipation of crossmodally-induced motor sequences B and A (the former decreasing interference, the latter decreasing facilitation). The importance of time in crossmodal consolidation paradigms was also highlighted in a study by Zhang et al (2011) who found that movement observation can enhance the consolidation of motor memories if observation takes place immediately after physical training, as opposed to 24 h after physical training. The time course and the underlying mechanisms of auditory-motor learning could be further explored in future studies, for example with a between-subject design, in which motor performance is tested at different time points in different groups, in order to avoid repeated motor testing.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, in our study, motor performance differences between groups could have decreased due to a time-based dissipation of crossmodally-induced motor sequences B and A (the former decreasing interference, the latter decreasing facilitation). The importance of time in crossmodal consolidation paradigms was also highlighted in a study by Zhang et al (2011) who found that movement observation can enhance the consolidation of motor memories if observation takes place immediately after physical training, as opposed to 24 h after physical training. The time course and the underlying mechanisms of auditory-motor learning could be further explored in future studies, for example with a between-subject design, in which motor performance is tested at different time points in different groups, in order to avoid repeated motor testing.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it has been suggested that the dPMC integrates sensory and motor information (Roland et al, 1980; Weinrich and Wise, 1982). Converging evidence from neuroimaging, neurostimulation, and neuropsychology indicates that the dorsal premotor cortex (dPMC) has a critical role in response selection (Bestmann et al, 2008; Halsband et al, 1993; O'Shea et al, 2007; Rushworth et al, 2003; Zhang et al, 2011). There is also considerable evidence that the left dPMC in particular plays a dominant role in visuomotor integration processes, while the right dPMC is subservient (Bestmann et al, 2008; Hardwick et al, 2013; Schubotz and von Cramon, 2002a, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…It may be the case that participants generate minimal movements when observing; this would make the current results even more intriguing by suggesting that such minimal movements do not interact with full sequence production. Moreover, even given M1 engagement in learning novel motor tasks by observation (Brown et al 2003;Cross et al 2006;Tkach et al 2007;Dushanova and Donoghue 2010;Zhang et al 2011) this does not necessarily indicate that the same units in M1 are engaged for mnemonic representation by observation or Figure 2. Experiment 1: timelines of the experiment and group mean levels of performance.…”
mentioning
confidence: 96%
“…The observation of action can lead to subsequent specific performance gains, presumably facilitating learning processes (Heyes and Foster 2002;Brown et al 2003;Torriero et al 2007;Hayes et al 2010;Zhang et al 2011). It is not clear, however, to what degree the beneficial effects of observation reflect a direct recruitment of the motor network involved in actual movement execution; specifically, whether the recruitment of the motor network through putative systems such as the "mirror neuron system," or an "action observation network" (AON) overlaps with the recruitment of the motor network in actual performance (Hari et al 1998;Buccino et al 2001;Calvo-Merino et al 2006;Gazzola and Keysers 2009;Mukamel et al 2010).This is a pertinent question given that there is increasing evidence that taskspecific changes in the motor cortex constitute an important part of the mnemonic representation of well-trained movement sequences (Karni et al 1998;Yang et al 2009Yang et al , 2014Xu et al 2010;Gabitov et al 2014) and that along Hebbian lines, neurons involved in task execution are an integral part of the subsequent mnemonic representation.…”
mentioning
confidence: 99%